Explorations in the Theology of Benedict XVI - Cavadini, John C. (Book collections on Project MUSE., 2012)
"Benedict XVI's writing as priest-professor, bishop, head of the Congregation for the Doctrine of the Faith, and now pope has shaped Catholic theological thought in the twentieth century. In Explorations in the Theology of Benedict XVI, a multidisciplinary group of scholars treat the full scope of Benedict's theological oeuvre, including the Augustinian context of his thought; his ecclesiology; his theologically grounded approach to biblical exegesis and Christology; his unfolding of a theology of history and culture; his liturgical and sacramental theology; his theological analysis of political and economic developments; his use of the natural law in ethics and conscience; his commitment to a form of interreligious dialogue from a place of particularity; and his function as a public, catechetical theologian. This volume originated at a conference at the University of Notre Dame on the occasion of the pontiff and theologian's eighty-fifth birthday. It provides an introduction to Benedict's ecclesially grounded theology, articulated in his essays, monographs, and sermons, and also serves as a primer in the major concerns of Catholic theological discourse in the twentieth century."--Publisher's description